China and India: Country role models of development success? - Amelia U. Santos-Paulino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The paper discusses views on China and India as country role models. In so doing the article recounts the economic and political reforms pursued by the two countries. The paper also outlines the outstanding reforms and the bottlenecks that could jeopardize economic performance and development going forward, drawing lessons for other developing countries.
Keywords: O2; O43; O53; D73; 330; China; India; reforms; growth; development; Entwicklung; Wirtschaftsreform; Politische Reform; China; Indien